2008
DOI: 10.1021/ja804365e
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the Mn(IV)/Fe(III) Cofactor of Chlamydia trachomatis Ribonucleotide Reductase by Extended X-ray Absorption Fine Structure Spectroscopy and Density Functional Theory Calculations

Abstract: The class Ic ribonucleotide reductase from Chlamydia trachomatis (Ct) uses a stable Mn(IV)/Fe(III) cofactor to initiate nucleotide reduction by a free-radical mechanism. Extended X-ray absorption fine structure (EXAFS) spectroscopy and density functional theory (DFT) calculations are used to postulate a structure for this cofactor. Fe and Mn K-edge EXAFS data yield an intermetallic distance of ~2.92 Å. The Mn data also suggest the presence of a short 1.74 Å Mn—O bond. These metrics are compared to the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
114
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(131 citation statements)
references
References 57 publications
(131 reference statements)
17
114
0
Order By: Relevance
“…CtR2 MnFe red showed opposite magnitudes (ϳ25%, ϳ50%) of contributions from these two distances. Similar metal-metal distances in CtR2 MnFe have previously been attributed to Mn(IV)/(III)Fe(III) (ϳ2.90 Å) and Mn(II)Fe(III) (ϳ3.3 Å) sites (29,30,66). Here, the ϳ2.90 Å distance mostly reflected the Mn(III)Fe(III) cofactor, because Mn(IV) contributions were small.…”
Section: Structure and Xpr Of The Mnfe Cofactor-the Xpr Kinetics Of Ctr2supporting
confidence: 79%
See 1 more Smart Citation
“…CtR2 MnFe red showed opposite magnitudes (ϳ25%, ϳ50%) of contributions from these two distances. Similar metal-metal distances in CtR2 MnFe have previously been attributed to Mn(IV)/(III)Fe(III) (ϳ2.90 Å) and Mn(II)Fe(III) (ϳ3.3 Å) sites (29,30,66). Here, the ϳ2.90 Å distance mostly reflected the Mn(III)Fe(III) cofactor, because Mn(IV) contributions were small.…”
Section: Structure and Xpr Of The Mnfe Cofactor-the Xpr Kinetics Of Ctr2supporting
confidence: 79%
“…Implications for X-ray Crystallography of Dimetal-Oxygen Cofactors-Our present and previous data (29,30,66) indicate that XPR of high-valent FeFe and MnFe sites in CtR2 and also in the standard type R2 protein from mouse can occur within seconds to minutes already under XAS conditions. The respective doses (at 80 K) are at least 100 times smaller than those resulting in radiation damage of amino acid groups (46,105).…”
Section: Structures Of Fefe and Mnfe Cofactors-ourmentioning
confidence: 54%
“…The velocity of x-ray photoreduction suggests a value close to 1 V (62). Interestingly, Mn(IV) is more rapidly reduced than Fe(III) (27,48). These results point to a Mn(IV) Ͼ Fe(III) Ͼ Mn(III) order of the oxidizing potentials.…”
Section: Mn-fe Electronicmentioning
confidence: 77%
“…95,[96][97][98][99][100][101] For recent reviews see. [102][103][104][105] Notably, it was shown that the reconstitution reaction proceeds via a Mn(IV)-Fe(IV) Intermediate state.…”
Section: Class Ic R2 Proteinsmentioning
confidence: 99%